Relationship between body composition, sprint performance and vertical jump tests in young elite soccer players - Gameiro, Pedro (2019)
Abstract of poster presented at the 2nd International Congress of CiiEM - Translational Research and Innovation in Human and Health Science. 11-13 June, 2017, Monte de Caparica, Portugal